2009
DOI: 10.3310/hta13380
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of methods of storing donated kidneys from deceased donors: a systematic review and economic model

Abstract: The conclusions drawn for the comparison of machine perfusion with cold storage depend on which trial data are used in the model. Owing to the lack of good research evidence that either ViaSpan or Soltran is better than the other, the cheaper, Soltran, may be preferable. In the absence of a cost-utility analysis, the results of our meta-analysis of the RCTs comparing ViaSpan with Celsior indicate that these cold storage solutions are equivalent. Further RCTs of comparators of interest to allow for appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 246 publications
0
49
1
1
Order By: Relevance
“…The split between these transitions is age dependent (as the likelihood of pre-emptive retransplantation decreases with advancing age; Table 152). The probability that a KTR in each age range is suitable for retransplantation was taken from table 32 of Bond et al, 384 which was, in turn, estimated from a figure in chapter 5 of the UK Renal Registry Eighth Annual Report. 385 It was then assumed that 20% of these KTRs would receive a pre-emptive retransplantation.…”
Section: Peninsula Technology Assessment Group Economic Assessmentmentioning
confidence: 99%
“…The split between these transitions is age dependent (as the likelihood of pre-emptive retransplantation decreases with advancing age; Table 152). The probability that a KTR in each age range is suitable for retransplantation was taken from table 32 of Bond et al, 384 which was, in turn, estimated from a figure in chapter 5 of the UK Renal Registry Eighth Annual Report. 385 It was then assumed that 20% of these KTRs would receive a pre-emptive retransplantation.…”
Section: Peninsula Technology Assessment Group Economic Assessmentmentioning
confidence: 99%
“…HMP techniques are still open to criticism with the suggestion of increased endothelial injury, as found in a recent study of porcine livers [89], risk of trauma to the vessels and the question of cost effectiveness compared to static storage techniques [90]. Nonetheless, it appears that HMP may hold a significant advantage in reducing CI injury compared to CS techniques.…”
Section: Hypothermic Machine Perfusionmentioning
confidence: 95%
“…The traditional preservation solution is a type of static cold crystalloid solution that contains impermeants to maintain osmoregulation and control edema, reactive oxygen species scavengers to prevent free radical damage, substrates to maintain energy and buffers to prevent acidosis, such as UW solution, which has become a gold standard (12). It has been reported that cold storage is a simple and effective method, which keeps the donor kidney stored for up to 24 h when the kidney is from a standard deceased donor (13).…”
Section: Discussionmentioning
confidence: 99%